Antioxidant Activity and Bioactivity (LC50) of Soursop Leaves Jelly Candy with Addition of Soursop Fruit Extract (Annona muricata L) - Yenrina, Rina; Sayuti, Kesuma; Putri, Rizky Astricia (Pakistan Journal of Nutrition, 2015)
It has been reported that the leaves of the soursop contains acetogenin that have the potential to inhibit the growth of cancer cells. Soursop leaves has not been used optimally, nowadays its leaves have only processed into tea or in capsules for drug treatment and also just to keep the body stamina. In this study had been tried to make Jelly Candy from the leaves, but there are weaknesses in flavor and taste. This study used a completely randomized design (CRD) consist of 5 treatments and 3 replications. Data were analyzed statistically used ANOVA and followed by Duncan’s New Multiple Range Test (DNMRT) at 5% significance level, the treatment were addition of soursop fruit extract as follows: A (0%), B (10%), C (20%), D (30%) and E (40%). Antioxidant activity was analyzed using DPPH method and bioactivity using Brine shrime Lethality Test (LC50). The results showed that the addition of the soursop fruit extract had significant effect on the antioxidants activity and bioactivity in the product was weak (LC50>1000 μg/mL).